Perilaku Adaptif dan Ritualisme Mahasiswa: Dinamika Perubahan Religiusitas di Lingkungan Sosial yang Menyimpang - Salma Salsabila; Nurut Fatimah (Integralistik, 2026)
This study aims to examine the reasons why university students continue performing religious rituals despite engaging in deviant behaviors, as well as to understand how early internalized religious values transform into adaptive practices within permissive social environments. Using a qualitative case study approach, data were collected through in-depth interviews with three primary informants and six additional informants from their close social circles. The findings reveal that early religious education such as TPQ, madrasah, or pesantren and strong familial involvement form a solid foundation of religiosity among the participants. Ritual practices such as prayer persist as a means of self-control, spiritual reflection, and maintaining a connection to religious values. The study identifies two forms of adaptive behavior: innovative adaptation, in which individuals maintain religious goals while adjusting their expressions in formal settings; and ritualistic adaptation, in which religious rituals continue even as students engage in deviant behaviors within close peer groups. These findings indicate that early internalization of religious values shapes students’ strategies for religious adaptation within socially liberalenvironments.